Recovery of dilute acetic acid via esterification reaction catalyzed by Amberlyst 15 - How, Teoh Wei (2013)
The recovery of acetic acid from its dilute aqueous solutions is a major problem in both petrochemical and fine chemical industries. The conventional physical separations such as distillation and extraction suffer from several drawbacks. In the present work, the esterification reaction of dilute acetic acid with 2-ethyl-1-hexanol has been studied in the presence of ion-exchange resin Amberlyst 15. The effect of important operating parameters such as speed of agitation and reaction temperature has been examined. Within the range of study, the maximum conversion of acetic acid reached 98.8% at temperature of 100°C. For speed of agitation, there is no much effect to the conversion of acetic acid ranging from 300rpm to 600pm where the highest conversion of acetic acid was 75%. Experimental kinetic data of the esterification reaction were correlated with the pseudo-homogeneous (PH), Langmuir-Hinshelwood-Hougen-Watson (LHHW) and Eley-Rideal (ER) models. The LHHW model gave the best agreement with the data. The activation energy for the reaction was found to be 71.08 kJmol-1.